2019
DOI: 10.18775/ijmsba.1849-5664-5419.2014.56.1001
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Website Service Quality on Customer Satisfaction Towards Online Shopping: The Mediating Role of Confirmation of Expectation

Abstract: Researching customer satisfaction becomes key for organizational competitiveness because satisfied customers become loyal customers. Therefore, it is important to measure customer satisfaction towards online shopping, since satisfied customers will make repetitive purchases and provide recommendations to others, thus generating the profit for a particular e-commerce company. Customer satisfaction towards online shopping can significantly be influenced by website service quality, hence many of the previous stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Results support the influential role of the choice factors such as university reputation, social life, course, and dealings with university contribute to influence student expectation and offset the effect of paying university fees. The result converges that consumer expectation of choice factor will directly affect perceived performance as demonstrated in marketing (Johnson et al, 1998), hospitality and tourism (Pizam & Milman, 1993) and in website service quality (Biswas et al, 2019). The result is consistent with studies that student satisfaction in colleges is strongly influenced by student expectations (Patterson & Johnson, 1993;Rolfe, 2002).…”
Section: Cost Of Study and Student -Consumer Expectation And Satisfactionsupporting
confidence: 85%
“…Results support the influential role of the choice factors such as university reputation, social life, course, and dealings with university contribute to influence student expectation and offset the effect of paying university fees. The result converges that consumer expectation of choice factor will directly affect perceived performance as demonstrated in marketing (Johnson et al, 1998), hospitality and tourism (Pizam & Milman, 1993) and in website service quality (Biswas et al, 2019). The result is consistent with studies that student satisfaction in colleges is strongly influenced by student expectations (Patterson & Johnson, 1993;Rolfe, 2002).…”
Section: Cost Of Study and Student -Consumer Expectation And Satisfactionsupporting
confidence: 85%
“…This phenomenon is due to the website's ability to hide low-quality information regarding the product, leading to the customers' purchase and exchange. The website design could be measured by providing information and facilitating purchasing activities effectively and efficiently (Biswas et al, 2019). H7: There is a positive relationship between website design and online purchasing satisfaction from a university student's perspective.…”
Section: Website Designmentioning
confidence: 99%
“…Customer satisfaction based on the website service quality with confirmation of customer expectation was measured in [36]. The results found that website service quality has a significant and positive relationship with confirmation of customers' expectations and their satisfaction level towards online shopping.…”
Section: The Servqual and E-servqual Dimensionsmentioning
confidence: 99%